Nutrition Education Regarding Physical Activity to Prevent Obesity Among Adolescents at State Islamic Senior High School 4 Banjar - Solechah, Siti Aisyah; Ali, Indra Haryanto; Setiawan, Muhammad Irwan; Yulidasari, Fahrini; Rahayu, Atikah; Tazkiah, Misna (Lambung Mangkurat University, 2024)
Lack of physical activity is one of the behaviors associated with non-communicable diseases. Physical activity levels decreased among individuals aged ten and above in South Kalimantan. The proportion of this problem also increased sharply in Banjar Regency. Discussions with the school showed that students at the school lacked physical activity. Nutrition education regarding physical activity has never been conducted at this school. This activity aimed to increase adolescents’ knowledge about the importance of physical activity in preventing obesity. It was conducted at Islamic Senior High School 4 Banjar, involving 67 members of the Youth Red Cross. Nutrition education was performed through lectures using PowerPoint slides. Participants' knowledge was assessed using pretest and posttest questionnaires. There was a significant knowledge difference (p<0.05) before and after the education. A total of 61 people had a higher score than before the education. A total of 52.2% of participants had poor knowledge, and 47.8% had moderate knowledge before education. After education, 58.2% had high knowledge, 38.8% had moderate knowledge, and 3% had low knowledge. It indicated that nutrition education is effective in increasing participants' knowledge.